Perioperative management for the prevention of bacterial infection in cardiac implantable electronic device placement - Katsuhiko Imai (Journal of Arrhythmia, 2016)
Cardiac implantable electronic devices (CIEDs) have become important in the treatment of cardiac disease and placement rates increased significantly in the last decade. However, despite the use of appropriate antimicrobial prophylaxis, CIED infection rates are increasing disproportionately to the implantation rate. CIED infection often requires explantation of all hardware, and at times results in death. Surgical site infection (SSI) is the most common cause of CIED infection as a pocket infection. The best method of combating CIED infection is prevention. Prevention of CIED infections comprises three phases: before, during, and after device implantation. The most critical factors in the prevention of SSIs are detailed operative techniques including the practice of proper technique by the surgeon and surgical team.